Phenomenon and Critical Conditions of Chamber Soil Sliming during EPB Shield Tunneling in Water-Rich Weathered Diorite: Case Study of Jinan Metro, China - Lu Wang; Wei Zhu; Yongjin Qian; Chao Xu; Jiannan Hu; Huitang Xing (Advances in Civil Engineering)
The sliming problem of chamber soil is caused by excessive groundwater seeping into the pressure chamber when an Earth pressure balance shield tunnels through a water-rich weathered rock stratum under semiopen under-pressure mode. As a solution to this problem, a calculation model was established based on field measurements of the discharged soil properties, the seepage water volume, and the seepage path in Jinan Metro, China. Chamber soil sliming is a phenomenon in which chamber soil is in a thin mud state, with no pressure balance in the pressure chamber of the EPB shield and an excessive water content of the chamber soil owing to the continuous seepage of groundwater into the chamber. The chamber pressure is relatively low, which is different from the phenomenon of spewing when the chamber pressure is relatively high. A large amount of water seepage from the stratum around the tunnel excavation surface and shield to the chamber is a significant factor leading to chamber soil sliming during the construction process. It was considered that when the moisture content of the chamber soil, w, is 2wL ≤ w ≤ 3wL, slight chamber soil sliming may occur, whereas when w ≥ 3wL, serious chamber soil sliming may occur. Moreover, some measures to prevent and control the occurrence of chamber soil sliming were discussed. Controlling the advancing time and the permeability coefficient of chamber soil during construction is the most effective measure to avoid the phenomenon of soil sliming.